1996
DOI: 10.1097/00007632-199607010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Familial Predisposition for Degenerative Disc Disease

Abstract: The results indicate that a familial predisposition to degenerative disc disease can exist along with other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 6 publications
2
23
1
3
Order By: Relevance
“…Other relevant studies have supported the idea that degenerative disc disorders may be genetically determined [9][10][11][12] . The first gene mutations associated with intervertebral disc degeneration in humans were reported in 1998 13) .…”
mentioning
confidence: 86%
“…Other relevant studies have supported the idea that degenerative disc disorders may be genetically determined [9][10][11][12] . The first gene mutations associated with intervertebral disc degeneration in humans were reported in 1998 13) .…”
mentioning
confidence: 86%
“…Biochemical differences in the composition of a disc might explain a familial predisposition to disc degeneration in general [13]. Other genetically influenced factors may be body habitus and physical characteristics [13], whereas non-genetically influenced and therefore confounding risk factors in this clinical report may be smoking [8] (patient 1) and performing a physically demanding job [2] (patient 1 and 2), as these are risk factors at least in lumbar disc herniation.…”
Section: Discussionmentioning
confidence: 82%
“…Other genetically influenced factors may be body habitus and physical characteristics [13], whereas non-genetically influenced and therefore confounding risk factors in this clinical report may be smoking [8] (patient 1) and performing a physically demanding job [2] (patient 1 and 2), as these are risk factors at least in lumbar disc herniation. Finally, we cannot exclude the possibility that the occurrence of a symptomatic thoracic disc herniation at the exact same level and early age in these brothers was merely coincidental, given the high prevalence (37%) of thoracic disc herniations in asymptomatic individuals [21].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several case-control studies 19,20 have described increased selfreporting of a family history of intervertebral disc disease (45% to 47%) among patients requiring surgery for disc herniations compared with controls (<33%). In a similar study, Matsui et al 8 reported that disc herniations in patients with a positive family history were more severe than those in controls (p < 0.03).…”
mentioning
confidence: 99%